Credit Management Implementation and Financial Performance of Microfinance Institutions in Calamba City - Lacuata, Carl Darren (Journal of Interdisciplinary Perspectives, 2024)
Microfinance institutions are vital to inclusive growth and development in the Philippines by providing tailored financial services to marginalized groups. Implementing credit management is crucial for their success since it can facilitate good financial performance while promoting financial inclusion, alleviating poverty, and driving rural development. The main objective of this study was to describe and determine the relationship between credit management implementation and the financial performance of microfinance institutions in Calamba City. This study used descriptive correlational design to describe the credit management implementation and financial performance levels of microfinance institutions in Calamba City and determine if there is any significant relationship between these two variables. With the aid of the G-power, the study was able to get 200 respondents based on a 0.2278 effect size and 95% degrees of confidence. The sample size was composed of management and clients of microfinance institutions and was selected using a simple random sampling technique. Data was collected through validated researcher-made questionnaires distributed personally to the respondents. The data gathered were treated using four-point Likert scales, mean, Independent T-test, and Pearson correlation coefficient. The study’s findings revealed that the microfinance institutions in Calamba City have fully implemented their credit management and exhibited very high financial performance. There was a significant relationship between the two variables. The r values ranging from .509 to .685 were interpreted as having a moderate positive correlation to credit management implementation and financial performance. As an output of the study, an action plan was proposed, a series of strategic activities intended to enhance the financial performance of microfinance institutions through credit management implementation.